1995
DOI: 10.1007/bf00926882
|View full text |Cite
|
Sign up to set email alerts
|

The effects of exogenous histamine in isolated rat hearts

Abstract: The role of histamine in cardiac physiology and pathophysiology is not clarified, but is dependent on species. The effects of exogenous histamine in Langendorff-perfused rat hearts were investigated. 1 mM, 100, 10, 1 and 0.1 microM of histamine (n = 7 each) as 15 min infusions were employed in a dose-response study, and compared to control perfused hearts (n = 7). In another experimental series, 100 microM histamine (n = 15) was added during reperfusion after 25 min global ischemia, and compared to control isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…These results suggested that, in the early stage of AMI, mast cells might not be the predominant source of increased histamine. In the cardiovascular system, histamine is documented to be vasoactive, inotropic, chronotropic, and arrhythmogenic 20 21 22 . However, a role for histamine in the pathogenesis of specific cardiovascular diseases remains controversial.…”
mentioning
confidence: 99%
“…These results suggested that, in the early stage of AMI, mast cells might not be the predominant source of increased histamine. In the cardiovascular system, histamine is documented to be vasoactive, inotropic, chronotropic, and arrhythmogenic 20 21 22 . However, a role for histamine in the pathogenesis of specific cardiovascular diseases remains controversial.…”
mentioning
confidence: 99%